Shri Shiv Shankar Mandir - Mumbai Archive Project Team (Jio Institute, 2024)
The wall of Shri Shiv Shankar Mandir wall bears the old name Kandivligaon, written in Devanagari script. The architecture of the temple is an eclectic mix. The temple’s north Indian-style shikhara (spire) appears to be a modern addition, rising incongruously over the sloped roof superstructure typical of Konkani vernacular architecture.